(untitled) (Al-NASR, 2023)
After the departure of the Holy Prophet (S.A.W), those ruling of the Muhammadan Shari’ah which were not definitive in terms of their proofs, arguments and correctness, or regarding which different sayings were interpreted by companions of Holy Prophet (S.A.W), or for the interpretation in revealed books and the word used in the Sunnah were likely to have more than one meaning. In the same way, many religious, social, economic and political problems and issues that did not exist for which there was no clarity of orders, the companions of the prophet used Ijtihad for their Shariah solution. Now, in view of the difference in the natural abilities of Ijetihad insight, thinking, inferring and extracting rulings, and in view of the different times differed needs of our respective times, disagreements occurred in numerous Ijtihad issues and problems. It laid the basis of disagreement between them. As a result of which many jurisprudential religions and different schools of thought came into existence, which created great ease and expansion for the Ummah. With the passage of time, the rest of the religions became extinct, but these four religions gained fame, popular acceptance and continued existence due to their multiple characteristics. Now, since every person is not capable of deriving rulings through Ijtihad and Qiyas, secondly, because the jurisprudential religions had different interpretations of the Qur’an and the Sunnah, the majority of the Islamic world started imitating one or the other of these religions and Masalik.